2021
DOI: 10.3389/fneur.2021.665136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neurofascin 155 Antibody-Positive Chronic Inflammatory Demyelinating Polyneuropathy/Combined Central and Peripheral Demyelination: Strategies for Diagnosis and Treatment Based on the Disease Mechanism

Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an immune-mediated demyelinating disease of the peripheral nervous system (PNS). A small number of CIDP patients harbors autoantibodies against nodal/paranodal proteins, such as neurofascin 155 (NF155), contactin 1, and contactin-associated protein 1. In most cases, the predominant immunoglobulin (IgG) subclass is IgG4. Node/paranode antibody-positive CIDP demonstrates distinct features compared with antibody-negative CIDP, including a poor response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 75 publications
(220 reference statements)
1
33
0
4
Order By: Relevance
“…The isoform of NF155 is more vulnerable to attack in immune modulatory dysfunction than other molecules in CIDP ( Delmont et al, 2017 ; Burnor et al, 2018 ; Kira, 2021 ). The IgG subclass was more frequently detected in both the anti-NF186 and anti-NF155 antibody-positive CIDP.…”
Section: Role Of the Node Of Ranvier And Neurofascin In Chronic Inflammatory Demyelinating Polyneuropathymentioning
confidence: 99%
See 4 more Smart Citations
“…The isoform of NF155 is more vulnerable to attack in immune modulatory dysfunction than other molecules in CIDP ( Delmont et al, 2017 ; Burnor et al, 2018 ; Kira, 2021 ). The IgG subclass was more frequently detected in both the anti-NF186 and anti-NF155 antibody-positive CIDP.…”
Section: Role Of the Node Of Ranvier And Neurofascin In Chronic Inflammatory Demyelinating Polyneuropathymentioning
confidence: 99%
“…A study showed that injection of anti-NF antibodies from patients with CIDP to the experimental autoimmune neuritis (EAN) model could enhance and prolong an ongoing neuritis, but injection of anti-NF antibodies to the control group is not pathogenic ( Ng et al, 2012 ). An electrophysiology test of CIDP showed that distal and F-wave latencies are influenced more severely than the motor conduction velocities and compound muscle action potential amplitudes and have a high frequency of spinal root hypertrophy on MRI images, which suggest that nerve terminals, major plexuses, and spinal roots are more frequently involved in patients with anti-NF155 antibody-positive CIDP, where the BNB is anatomically absent or loose ( Ogata et al, 2015 ; Kira, 2021 ). The BNB maintains nerve homeostasis by preventing the free movement of soluble proteins in the circulation into the endoneurium microenvironment under normal physiological conditions.…”
Section: Role Of the Node Of Ranvier And Neurofascin In Chronic Inflammatory Demyelinating Polyneuropathymentioning
confidence: 99%
See 3 more Smart Citations